MAQĀṢID- BASED ISLAMIC BOARDING SCHOOL MODEL AL- SYARĪ'AH: LITERATURE ANALYSIS ON THE ROLE OF ISLAMIC BOARDING SCHOOLS IN SHAPING THE CHARACTER OF STUDENTS - Galby Silvia Rachmah; Zamroni Zamroni; Imroh Atul Musfiroh (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Islamic boarding school-based model maqāṣid al-syarī'ah as a framework for character education for Islamic boarding school students in the digital era. The study was conducted using a qualitative descriptive method with a descriptive approach. library research on various Islamic boarding school and Islamic education literature. The analysis was conducted through the stages of identification, selection, and interpretation to find the relevance of Islamic values. maqāṣid al-syarī'ah in the Islamic boarding school education system. The results of the study show that the implementation of the five main principles— ḥifẓ ad-dīn , ḥifẓ an-nafs , ḥifẓ al -' aql , ḥifẓ an-nasl , And ḥifẓ al- māl —forms the foundation for the formation of the spiritual, moral, and intellectual character of students. Curriculum integration, holistic pedagogy, and external collaboration strengthen Islamic boarding schools as adaptive and globally competitive Islamic educational institutions. In conclusion, this model has the potential to become a strategic paradigm in the development of Islamic education that balances traditional values and modern innovation.